EFFECT OF VITAMIN E ON CREATINE KINASE POST-EXERCISE IN ADULT - Molenaar, Monica Caroline; Wahyuni, Nila (Sport and Fitness Journal, 2024)
Introduction: Exercise is well-known for its benefits to strengthen muscle and improves whole-body energy metabolism. Increased creatine kinase (CK) level in blood is an indicator of skeletal muscle damage induced by strenuous physical exercise. It is known that vitamin E plays a key role as strong antioxidant which can be considered as the solution to attenuate exercise-induced muscle tissue damage by reducing creatine kinase (CK) concentration. Method: The literature search was performed using several databases: Research Gate, PubMed, and Google Scholar. The following search terms were used: “exercise”, “vitamin e”, “creatine kinase”, “exercise-induced muscle damage” and “muscle soreness”. Results: There were 7 articles obtained and analyzed in this literature review which showed various results regarding the effect of vitamin E on creatine kinase (CK) level post-exercise especially in adult. Discussion: There were still inconsistence results of vitamin E which can decrease serum creatinine kinase after exercise. Some studies showed that 250 mg of vitamin E administration 1 hour before exercise were effective in reducing creatine kinase (CK) after moderate exercise. In contrary, another study revealed that there was no beneficial effect on creatine levels after administration of 235 mg vitamin E combined with 1000 mg of vitamin C 2 hours prior to exercise in runners over 30 years of age.